The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s10495-015-1150-0
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates palmitate-induced apoptosis in MIN6 pancreatic β-cells through PI3K/Akt/FoxO1 and mitochondrial survival pathways

Abstract: Lipotoxicity plays a vital role in development and progression of type 2 diabetes. Prolonged elevation of free fatty acids especially the palmitate leads to pancreatic β-cell dysfunction and apoptosis. Curcumin (diferuloylmethane), a polyphenol from the curry spice turmeric, is considered to be a broadly cytoprotective agent. The present study was designed to determine the protective effect of curcumin on palmitate-induced apoptosis in β-cells and investigate underlying mechanisms. Our results showed that curc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 50 publications
7
49
0
Order By: Relevance
“…Importantly, a recent clinical trial demonstrated that curcumin intervention in pre-diabetic human subjects lowered the number of individuals who eventually progressed to T2D [18] . Numerous in vitro investigations [17,[20][21][22][23][24][25][26] . For example, Pan et al investigated the protective effects of the curcumin derivative C66 on diabetic cardiomyopathy.…”
Section: Dietary Polyphenol and Dietary Polyphenol Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a recent clinical trial demonstrated that curcumin intervention in pre-diabetic human subjects lowered the number of individuals who eventually progressed to T2D [18] . Numerous in vitro investigations [17,[20][21][22][23][24][25][26] . For example, Pan et al investigated the protective effects of the curcumin derivative C66 on diabetic cardiomyopathy.…”
Section: Dietary Polyphenol and Dietary Polyphenol Interventionmentioning
confidence: 99%
“…We found that this shortterm curcumin treatment effectively ameliorated muscular oxidative stress by activation of the anti-oxidative Nrf2 signaling cascade [27] . A recent study by Hao et al demonstrated that in the mouse pancreatic MIN6 β-cell line, curcumin attenuated palmitate-induced cell death, possibly via the activation of cell survival Akt signaling and the inhibition of nuclear translocation of FoxO1 [26] .…”
Section: Dietary Polyphenol and Dietary Polyphenol Interventionmentioning
confidence: 99%
“…Bcl-2 is one of antiapoptotic Bcl-2 family proteins, which regulates the mitochondrial pathway [33]. Several studies showed that curcumin can block the oxidative stress mediated apoptosis via suppressing the mitochondria apoptotic pathway against cisplatin, palmitate and 6-hydroxydopamin induced cytotoxicity [47][48][49]. These data indicated that curcumin protected L02 cells against FZD induced apoptosis via inhibiting mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 96%
“…In lung cancer, curcumin induces apoptosis accompanied by changes in intracellular oxidative stress-related enzymes and also by phosphorylation and activation of the mitogen-activated protein kinase signaling pathway factors c-Jun N-terminal kinase, p38, and extracellular signal-regulated kinase (Yao et al 2015). In pancreatic B cells, curcumin attenuates palmitate-induced apoptosis through PI3K/AKT/Fox01 and mitochondrial survival pathways (Hao et al 2015). A decrease in ROS with a concomitant increase in various antioxidant and DNA repair genes, such as BRCA-1, H2AFX, and PARP-1, were observed after curcumin treatment (Jain et al 2015).…”
Section: Curcuminmentioning
confidence: 99%